Enhancing curriculum relevance and student engagement: the role of lecturers as agents of change in higher education - Micallef, Bernard (Frontiers in Education, 2025)
This study investigates the role of lecturers as change agents in higher education, focusing on their ability to improve curriculum relevance and student engagement within rigid institutional structures. Using a constructivist grounded theory approach, qualitative data were collected through in-depth interviews with lecturers and analyzed using in-vivo and open coding, culminating in the development of the Conditional Matrix. The findings reveal that lecturers who integrate real-life experiences, foster collaboration, and adopt innovative teaching strategies, such as flipped classrooms, significantly enhance student engagement, critical thinking, and curriculum relevance. However, challenges such as resistance to change among faculty and outdated module descriptors were identified as barriers to progress. The study emphasizes the importance of granting lecturers greater autonomy in curriculum development and providing targeted professional development to align education with industry demands. Ultimately, empowering lecturers is essential to preparing students for the modern workforce and ensuring higher education remains relevant and impactful.